Rewrapping Indianness for Spain: The Peritextual Representation of Native North American Identity in Literary Translations - Herrero López, Isis (TTR, 2015)
When literature gets translated and published in the target market, the peritextual elements of the books get modified and updated because of commercial and aesthetic issues. If the translation involves identities very different from that of the target culture, then the peritexts offer a great amount of information about the ethnic representations that are accepted, welcome and customary as for the identities of the source culture and its members. This paper analyzes such a situation in relation to the Spanish translations of Native American written literature. By means of examining the peritexts of the available renditions in Spain, it is possible to establish if the publishing houses share a common image of Indianness, how it and its alternatives are used linguistically and visually, and what are the consequences of those cultural representations. This paper also includes a revision of the convergence of Translation Studies, Native American Studies and Imagology Studies in researching these renditions, and it stresses the importance of using this multidisciplinary point of view on the research materials.